1998
DOI: 10.1016/s0022-5223(98)70401-5
|View full text |Cite
|
Sign up to set email alerts
|

A New Artificial Placenta with a Centrifugal Pump: Long-Term Total Extrauterine Support of Goat Fetuses

Abstract: We believe that this system can be used for experimental models of the fetus and will come into clinical application for fetal extrauterine support systems and backup systems for fetal operations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
37
1
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 21 publications
1
37
1
1
Order By: Relevance
“…PO2 values of UA and UV in the goat fetus are known to range from 17.3 to 24 mmHg and from 30 to 33 mmHg, respectively. Fetal baseline data shown in Table 1 are in agreement with those of previous studies (4,9). PCO2 values were higher than normal values probably due to the higher CO2 production in the room air outside the uterus.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…PO2 values of UA and UV in the goat fetus are known to range from 17.3 to 24 mmHg and from 30 to 33 mmHg, respectively. Fetal baseline data shown in Table 1 are in agreement with those of previous studies (4,9). PCO2 values were higher than normal values probably due to the higher CO2 production in the room air outside the uterus.…”
Section: Discussionsupporting
confidence: 90%
“…PCO2 values were higher than normal values probably due to the higher CO2 production in the room air outside the uterus. Oxygen consumptions of the fetuses were camparable to those of the previous study (4). However, oxygen delivery was higher and oxygen extraction ratio was lower than the values by Kuwabara et al (10) probably due to the high pump flow rate.…”
Section: Discussioncontrasting
confidence: 59%
“…Fetal cardiac surgery, which might be a big challenge in the future, deals, for example, with cardiopulmonary bypass. [13][14][15] Fetal cardiocentesis is one of the three methods of fetal intravascular access that are generally employed (the others being cordocentesis and cannulation of the intrahepatic portion of the umbilical vein). As these methods are invasive, thorough preoperative preparation is needed.…”
Section: Introductionmentioning
confidence: 99%
“…The use of an artificial placenta has been proposed, but previous studies have had limited success, possibly because the circuit volume was too large and the resistance of the circuit was too high (1)(2)(3)(4)(5). A more compact circuit may be a solution; in 2009, Reoma et al reported a 4-h survival period using a pumpless artificial placenta for the first time (6).…”
mentioning
confidence: 99%